Minimizing communication risk in construction: a Delphi study of the key role of project managers - Ceric, Anita (Journal of Civil Engineering and Management, 2014)
All significant construction projects involve the project owner and the contractor, as well as their project managers. Following upon recent research into the multiple principal-agent problem, which was applied to the minimization of communication risk in construction projects, the focus here is on communication issues between the four project parties. Recent research has shown that the relationship between the project owner and the contractor is paramount for risk minimization before the contract between them is signed. However, the relationship between project managers is dominant for risk minimization after the contract is signed. To further explore risk minimization at this stage of the project, the Delphi method was employed. A panel of highly-experienced project managers working for both project owners and contractors was asked several rounds of questions in an attempt to arrive to a consensus concerning the most important relationships between project parties in terms of risk minimization after the contract is signed. The relationship between the two project managers tops the ranking, thus focusing further research. As they are both agents, and as there is no contract between them, this offers a fresh challenge for the principal-agent theory.